(untitled) (International Journal of Scientific Trends, 2024)
Analysis and generalization of materials on hydrodynamic systems in the oil and gas regions of Uzbekistan. Application of mathematical statistical methods in processing geological and technological data. The properties of water-oil emulsions were utilized to evaluate the performance of the hydrodynamic system under elastic pressure conditions. By comparing the fluids extracted from the reservoir through the filtration hydrodynamic system, the actual and calculated values of reservoir pressure variation range from 1.21 to 2.5. For objects with an ellipsoidal hydrodynamic system, these values vary from 3.1 to 4.7. For the geological-physical and technological conditions of the Northern Urtabulak field, the flow coefficient is equal to 1.91. By intensifying fluid extraction from the reservoir with underlying water, it is possible to double the production capacity. The obtained results make it possible to assess the efficiency level of the hydrodynamic system, predict reservoir performance modes, select fluid extraction rates, and determine the necessary measures to maintain reservoir pressure. These results are recommended for use in developing oil field operation projects by "O’zLITIneftgaz" JSC during the process of reserves calculation, to justify reservoir operation modes and oil recovery factors. Additionally, they are recommended for use by "IGRNIGM" JSC to substantiate methods of reservoir impact and the rates of fluid extraction.